Expanding the limit, we get (x^2+2x∆x+∆x^2-2x-2∆x+1-x^2+2x-1)/<span>∆x
Crossing the 1s , the 2xs, and the x^2s out, we get
(2x</span>∆x+∆x^2-2∆x)/<span>∆x
Dividing the </span><span>∆x, we get
2x+</span><span>∆x-2.
Making the limit of </span><span>∆x=0, we get 2x-2.</span>
Answer:
I'm sorry I don't have answer but.
it's not C!
it could be 5 root 16? im not sure
Johnny ate 8 pies in 5 minutes
He must have ate 1 pie in (5/8) minutes
(5/8) minutes = 5/8 * 60 = 75/2 = 37.5 seconds
On each pie he spent 37.5 seconds.